2016
DOI: 10.1037/xhp0000216
|View full text |Cite
|
Sign up to set email alerts
|

Toward an integrative model of talker normalization.

Abstract: Successful speech perception requires accurate mapping of speech signals to linguistic categories despite talker variation in signals. Although factors like intrinsic and context cues have been identified, a full understanding of talker normalization remains to be achieved. In particular, it is important to examine the cocontribution of intrinsic, extrinsic and other cues in an integrative way. In Experiment 1, we examined the effect of intrinsic cues and typicality of a talker’s F0 range relative to populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 72 publications
(212 reference statements)
4
38
0
Order By: Relevance
“…This distinction between the lexical-semantic and indexical pathways is closely aligned with recent proposals concerning spoken language processing (Belin et al, 2004(Belin et al, , 2011Martin et al, 2016;Sumner et al, 2014;Van Berkum et al, 2008) and in broad agreement with the proposal that speech perception involves parallel representations of indexical and linguistic information (e.g., Magnuson & Nusbaum, 2007;Pierrehumbert, 2016;Zhang & Chen, 2016). For instance, based on a range of cognitive and neuro-cognitive studies, colleagues (2004, 2011) propose that speech input is processed by three parallel processing pathways that respectively perform analysis of (i) speech information, (ii) vocal identity, and (iii) vocal affective information.…”
Section: Implications For Models Of Spoken Word Comprehensionsupporting
confidence: 63%
“…This distinction between the lexical-semantic and indexical pathways is closely aligned with recent proposals concerning spoken language processing (Belin et al, 2004(Belin et al, , 2011Martin et al, 2016;Sumner et al, 2014;Van Berkum et al, 2008) and in broad agreement with the proposal that speech perception involves parallel representations of indexical and linguistic information (e.g., Magnuson & Nusbaum, 2007;Pierrehumbert, 2016;Zhang & Chen, 2016). For instance, based on a range of cognitive and neuro-cognitive studies, colleagues (2004, 2011) propose that speech input is processed by three parallel processing pathways that respectively perform analysis of (i) speech information, (ii) vocal identity, and (iii) vocal affective information.…”
Section: Implications For Models Of Spoken Word Comprehensionsupporting
confidence: 63%
“…One possibility is that the variable and dynamic nature of lexical tones made it more difficult for participants to learn/abstract than segments. As a result, the intervening sleep between training and later posttests thus facilitated the stimuli produced by the trained talker, which were also perceptually challenging [22,23,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Different from segments (consonants and vowels), as illustrated in Fig 1, lexical tones are highly dynamic, requiring listeners to evaluate the pitch they hear in the signal against the pitch range of the talker and continuously update this evaluation as more of the pitch contour is heard over time [21][22][23][24][25]. Importantly, a given talker shows variability in the production of tonal categories, thus also requiring listeners to evaluate the pitch they hear against the talker's different realizations of the same tonal categories (within-category variations) and of different tonal categories (crosscategory variations) [26][27][28][29][30][31][32]. Thus, listeners need to extract the abstract representations from tonal exemplars in order to generalize successfully across talkers [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been found that tonal language speakers rely on the relative pitch height of a tone with reference to a speaker's pitch range in lexical tone perception (Zhang et al 2012(Zhang et al , 2013Zhang and Chen, 2016). Similarly, relative pitch relationship is critical for musical perception.…”
Section: Introductionmentioning
confidence: 99%